Desenvolvimento de queijo cremoso caprino com potencial simbiótico - Barbosa, Ilsa Cunha (2016)
Probiotic cultures are described as single species or multiple species of microorganisms that when used for animals or man in appropriate amounts provide health benefits by promoting improvement in characteristics of the natural intestinal microflora. Prebiotics are non-digestible food components that reach the colon and selectively stimulate the proliferation or activity of populations of bacteria present there. A food classified as symbiotic constitutes one in which probiotics and prebiotics are combined in pre-established adequate amounts. This study was prepared creamy goat cheese with symbiotic potential, and evaluated the effects of the incorporation of probiotics Lactobacillus acidophilus LA-05 and Bifidobacterium lactis BB-12 and the prebiotic inulin on technological parameters, physico-chemical, microbiological and sensory product with 7 and 21 days of refrigerated storage (7 ± 1 ° C). Three were prepared cream cheese treatments goat with symbiotic potential: with 8 g / 100 g of inulin and Lactobacillus acidophilus (QLA); 8 g / 100 g of inulin and Bifidobacterium lactis (QBB); 8g / 100g inulin, L. acidophilus LA-05 and B. lactis BB-12 (QLB) co-culture plus cheese control (QC) added only the starter strain Lactococcus lactis subsp. cremoris and Lactococcus lactis subsp. lactis. The formulation of cheeses made allowed the preparation and filing with the INPI of an application for patent entitled "Cream cheese functional Goat milk and procurement process." L. counts acidophilus LA-05 and B. lactis BB-12 were greater than 6 log CFU / g, while the quantity of insulin was greater than 6 g / 100 g in cheese symbiotic with 7 and 21 days of storage. The firm reduced the synbiotic cheeses providing improved consistency of cream cheese. The evaluated cheeses showed high brightness values (L *), with a predominance of yellow (b *). QC showed a higher protein content, lipids and minerals compared to the others. A decrease of short-chain fatty acids and an increase of medium chain and long chain synbiotics in cheese compared to QC. There was an increase in the amount of linoleic acid conjugate in QLA, QBB and QLB. The highest values for depth of proteolysis, as well as the biggest changes in the release of free amino acids were found in QLB. The addition of inulin and probiotics did not affect the acceptance of the product. Inulin, L. acidophilus and B. lactis may be used together for production of synbiotic creamy goat cheese without detrimental effect on the general characteristics of the product quality associated with adding value to their functional potential